Editorial Notes - Mishra, Indira (JODEM: Journal of Language and Literature, 2024)
Editorial Notes It is a matter of pleasure to announce the publication of Vol. 15, No. 1, Issue 17 of Language and Literature Special Journal JODEM (The Journal of the Department of English Mahendra Multiple Campus, Dharan). This JODEM Issue has included 11 different research-based articles reflecting nine subject realms. Of the eleven articles, four are related to common issues, especially ethnicity and marginalization. The remaining seven articles are distinctly different in terms of the issues they are dealing with. The four articles by Asmita Bista, Man Kumar Rai, Jiwan Kumar Rai Tara Lal Shrestha, and Bidhya Shrestha have a commonality in their subject treatment i.e. the marginalization and ethnic identity. Achyut Bhattarai's article deals with translating legal documents into English to increase the readership among the intellectuals within and outside Nepal. Anupa Wagle's article is about ecology and raising awareness in individuals. Hem Lal Pandey is dealing with pedagogical issues. His article focuses on the conventions of academic writing in the context of Nepal. Unlike the other articles, M. K. Pokhrel's article analyzes the Hindu Sacred Book Srimad Bhagavata Mahapurana's one episode viz. "Sri Krishna Lila." Likewise, M. K. Tumbahang has taken up a sociolinguistic issue i.e. honorific system in the Limbu language. R. K. Gurung's article discusses the rationale behind using lowercase in the poems by E. E. Cummings and Ray Young Bear. Ramji Timalsina's article attempts to point out the elements of modernity in the poems of the Nepali great poet Laxmi Prasad Devkota. Most articles in this volume are based on analytical reading of the Nepali literary texts. To be exact, eight of eleven articles are based on the Nepali literary text whether ancient or modern. They have rightly focused on diverse aspects such as culture, religion, lifestyle, the hardship of life, struggle for identity, the pervasive chauvinistic outlook in Nepali society, or center versus marginal cases in or across communities. The Editorial Team fairly anticipates that this issue of JODEM can be of certain help in its related subjects and fields. Last but not least; the Team cordially thanks all the individuals and institutions - too many unfortunately to mention names - for their best wishes and cooperation. Thank you!